Issues of Formation and Distribution the Profit of Economic Entities - Mirkhalilovna, Ismailova Makhbuba (Research Parks Publishing LLC, 2022)
Modern world economic trends, globalization processes, business integration require the standardization of financial information that reflects the performance of companies participating in the internationalf market of goods and capital. In the context of developed market relations, organizations, including business entities, generate financial information aimed at a wide range of internal and external users in order to make various management decisions on strategic management to quickly and profitably attract investment, including foreign investment and expand business offer.